Young people's experience of online therapy for first‐episode psychosis: A qualitative study. (12th July 2021) - Valentine, Lee; McEnery, Carla; O'Sullivan, Shaunagh; D'Alfonso, Simon; Gleeson, John; Bendall, Sarah; Alvarez‐Jimenez, Mario
Abstract : Objectives: This study aimed to understand how young people with first‐episode psychosis experienced online therapy on a Moderated Online Social Therapy (MOST) platform known as Horyzons. Methods: Semi‐structured in‐depth qualitative interviews were conducted with 12 young people who had previously participated in Horyzons, a randomized controlled trial (RCT) of a long‐term digital intervention for first‐episode psychosis. Interviews were analysed using a phenomenological approach. Results: This study found that the online therapy experience for first‐episode psychosis was idiosyncratic, taking on different meaning for different users. The relatively fixed therapeutic content led to experiences that included on‐demand help‐seeking, positive distraction, revision, generalization and translation, and normalization. We also found that although the experience of online therapy was motivating to some, it was overwhelming for others. Conclusions: The self‐directed and flexible nature of the Horyzons online therapy gave some young people a sense of welcomed control over their mental health journey, and others felt overwhelmed by the high level of choice. Feeling overwhelmed by the level of choice appeared to interrupt their engagement with the platform, and thus their overall ability to use the intervention meaningfully. We also found that on‐demand help‐seeking and positive distraction were two functions unique to young people through online therapy and may have been related to the significant reduction in the number of overall presentations by young people to emergency departments and a non‐significant trend for lower hospitalizations due to psychosis in the intervention group of the Horyzons RCT. Practitioner points: Young people used online therapy for on‐demand support to help deal with distress. Young people used online therapy to distract themselves from distress in a positive way. Some young people valued the flexibility of online therapy, which increased their motivation to engage with it. Some young people were overwhelmed by the amount of choice available to them via online therapy, which decreased their motivation to engage.